Mind, Heart and Soul in the Fight Against Poverty - Marshall, Katherine; Keough, Lucy (Washington, DC: World Bank, 2013)
The world of religion has been unacknowledged and often unseen by many development practitioners. The areas of common concern and activity, though, are numerous and have great importance in the global effort to fight poverty. This book explores the diversity of collaboration between faith institutions and development agencies. ranging from community level interventions in support of excluded populations, work on education, health, and HIV/AIDS, restoring communities after conflicts, and global efforts to bring greater clarity and meaning to challenges such as poor country debt, labor and the struggle against poverty. What is emerging is a set of new partnerships that are founded on common concerns for the welfare of poor communities and the global cause of social justice. The need for broader and clearer insight, and for creative efforts to see and understand the whole, emerge as fundamental lessons of recent decades of development experience. This report seeks to delve more deeply into these lessons, stressing the centrality of faith in the human experience.